2017
DOI: 10.3390/su9101825
|View full text |Cite
|
Sign up to set email alerts
|

Rural Electrification Efforts Based on Off-Grid Photovoltaic Systems in the Andean Region: Comparative Assessment of Their Sustainability

Abstract: Abstract:In this paper, we comparatively assess the sustainability of rural electrification efforts based on off-grid solutions in Chile, Ecuador, and Peru. Our assessment considers four dimensions of sustainability (institutional, economic, environmental, and socio-cultural). We found that Ecuador and Chile have consistently failed to ensure mechanisms for the operation and maintenance of the deployed off-grid systems, which has made these solutions in poor Chilean and Ecuadorian communities inevitably unsust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The same argument applies for governments trying to electrify rural communities [52] that have no power-programs knows as rural electrification programs [53], reduce diesel consumption in communities that rely on diesel [8], or completely displace diesel in these communities [54]. Table 5 indicates that using a MSOC 20 percent reduces the net present cost of single home to nearly $70,000 compared with $117,000 when a MSOC of 50 percent was used.…”
Section: Nocturnal Load Resultsmentioning
confidence: 95%
“…The same argument applies for governments trying to electrify rural communities [52] that have no power-programs knows as rural electrification programs [53], reduce diesel consumption in communities that rely on diesel [8], or completely displace diesel in these communities [54]. Table 5 indicates that using a MSOC 20 percent reduces the net present cost of single home to nearly $70,000 compared with $117,000 when a MSOC of 50 percent was used.…”
Section: Nocturnal Load Resultsmentioning
confidence: 95%
“…The feasibility is a key factor because of high investment. In Chile, although technical standards for rural electrification are defined [6], they are not mandatory; consequently, government programs need to include cooperation, transferring know-how, and training. Also, implementation of an off-grid PV system may be beneficial to promote local economic development when the electrical grid is not an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, batteries increase the capital and operational cost, and the final disposal of batteries may produce high environmental impact [11,42]. In Chile, battery disposal is voluntary, but there is not much recycling infrastructure [6]; however, in other similar countries as Peru and Ecuador, some References [43,44] have reported that batteries have been found abandoned and buried in rural areas. The PV system should instead supply electricity directly into the pumping system.…”
Section: Effects Of Installation Of Pv System On Irrigation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of technical field questions is designed to assess the apparent instantaneous health of components. In addition, technical sustainability is widely regarded as effected by system use and the appropriateness of the initial system design [49].…”
Section: Technical Sustainability Factormentioning
confidence: 99%